Clinical Characteristics of Patients With Cancer Referred for Outpatient Physical Therapy. Issue 4 (1st April 2015) - Alappattu, Meryl J.; Coronado, Rogelio A.; Lee, Derek; Bour, Barbara; George, Steven Z.
Abstract : Background: Cancer rehabilitation is a developing area, with an increasing number of survivors of cancer in the United States. The increase in survivorship occurs alongside impairments arising directly from cancer or from treatment-related side effects. Objective: This study described clinical characteristics of patients with cancer referred for outpatient physical therapy and explored patterns in frequency of impairments between type of cancer and mode of cancer treatment. Design: This was a retrospective chart review of patients with cancer referred to a tertiary care physical therapy clinic over a 2-year period. Methods: Characteristics such as age, sex, cancer type, mode of treatment, and neuromusculoskeletal impairments were identified. Impairment frequencies were computed based on cancer type and mode of treatment. Results: Data from 418 patients (mean age=57.9 years, SD=14.3; 41.1% female) were examined. Genitourinary cancer (n=169) and breast cancer (n=90) were the most prevalent types of cancer reported in this sample. Impairments in strength (83.6%) and soft tissue (71.3%) were the most common examination findings. Lymphedema was most common in patients with breast cancer, and incontinence was most common in patients with genitourinary cancer. Limitations: The types of cancer identified in this study may be reflective of this tertiary center and may not generalize to other facilities. Impairment identification during the initial physical therapist evaluation was not performed systematically. Conclusion: These data reinforce that physical therapists should screen for lymphedema in patients with breast cancer and incontinence in urogenital cancers. Strength and soft tissue integrity should be evaluated in most patients with cancer. Assessing pain and fatigue levels is recommended for patients who have had radiation therapy.